-6u+7=u+70

Simple and best practice solution for -6u+7=u+70 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6u+7=u+70 equation:


Simplifying
-6u + 7 = u + 70

Reorder the terms:
7 + -6u = u + 70

Reorder the terms:
7 + -6u = 70 + u

Solving
7 + -6u = 70 + u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-1u' to each side of the equation.
7 + -6u + -1u = 70 + u + -1u

Combine like terms: -6u + -1u = -7u
7 + -7u = 70 + u + -1u

Combine like terms: u + -1u = 0
7 + -7u = 70 + 0
7 + -7u = 70

Add '-7' to each side of the equation.
7 + -7 + -7u = 70 + -7

Combine like terms: 7 + -7 = 0
0 + -7u = 70 + -7
-7u = 70 + -7

Combine like terms: 70 + -7 = 63
-7u = 63

Divide each side by '-7'.
u = -9

Simplifying
u = -9

See similar equations:

| y/5=-20 | | 11u+1=6u-29 | | -x-4=-4x+2 | | -8g+7=-g+63 | | 70=6x-14 | | 7j-4=3j-28 | | 10e-4=4e-10 | | 2a+4=-3a-36 | | -2q+6=3q-24 | | 2x-1=-x-28 | | 6h-4=h-9 | | 9y-1=5y+15 | | 12+8=5d+57 | | 7(3g+8)/4=35 | | 8-32x+27x-3=0 | | 4(x-5)=-1.6 | | 12d+8=8d+16 | | 13=5c-9 | | 9e-7=28.1 | | 8(x-2)=26.4 | | 2(3y-6)=-18 | | 2(7v-4)=-22 | | 3(4k-4)=60 | | 4(6u-4)=152 | | 3(5t+2)=-84 | | 5(4q+3)=-145 | | 8e-7=17 | | 16.2=2c-2 | | 5(4x-4)=-40 | | 3(4f+1)=-21 | | 5(3s-2)=-145 | | 6e-4=14 |

Equations solver categories